Designing digital computing systems with Verilog - Lilja, David J. (Cambridge University Press, 2005)
Using Verilog, a leading commercial hardware description language, this text describes how to specify, design, and test a complete digital system. After a brief introduction to the Verilog language, the instruction set architecture (ISA) for the simple VeSPA (Very Small Processor Architecture) processor is defined. The remainder of the book demonstrates how both behavioral and structural models can be developed and intermingled in Verilog.